2017
DOI: 10.1002/ange.201610605
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric 1,3‐Dipolar Cycloaddition of β‐Fluoroalkylated α,β‐Unsaturated 2‐Pyridylsulfones with Nitrones for Chiral Fluoroalkylated Isoxazolidines and γ‐Amino Alcohols

Abstract: 2-Pyridylsulfone-and fluoroalkylated group-activated olefins underwent highly efficient diastereo-and enantioselective 1,3-dipolar cycloadditions across various aromatic and aliphatic nitrones in the presence of ac hiral Ni II / bis(oxazoline) catalyst. The process was tuned by 4 molecular sieves,chiral bis(oxazoline) ligands,reaction solvents,and temperature.Awide arrayo fo ptically pure fluoroalkylated isoxazolidines were obtained, thus facilitating the asymmetric synthesis of an enantioenriched a-trifluorom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…When we initially used 1 a and azomethine imine 1,3‐dipole 2 a for chiral N,N′ ‐bicyclic pyrazolidinone under Lewis acidic and 4 Å MS conditions, very low enantioselectivity and yield were observed. Control experiment in CH 2 Cl 2 revealed that 4 Å MS has a detrimental effect on the yield and diastereoselectivity (Table , entry 1), which is quite different from our previous investigation with nitrones …”
Section: Resultscontrasting
confidence: 90%
“…When we initially used 1 a and azomethine imine 1,3‐dipole 2 a for chiral N,N′ ‐bicyclic pyrazolidinone under Lewis acidic and 4 Å MS conditions, very low enantioselectivity and yield were observed. Control experiment in CH 2 Cl 2 revealed that 4 Å MS has a detrimental effect on the yield and diastereoselectivity (Table , entry 1), which is quite different from our previous investigation with nitrones …”
Section: Resultscontrasting
confidence: 90%
“…This reaction forms the N-O double bond and creates a stable nitronate intermediate, which can be isolated or used directly in subsequent reactions (Murahashi and Imada, 2019). One of the most notable characteristics of nitrones is their ability to undergo 1,3-dipolar cycloaddition reactions with alkenes or alkynes, known as the "nitrone-alkene/alkyne" cycloaddition (Yang, et al, 2017;Alshreimi, et al, 2020). This reaction forms isoxazolidine or isoxazole derivatives, depending on the specific conditions used (Qaddo and Abed, 2022;Li, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrones are widely used in the synthesis of natural products, pharmaceuticals, and other biologically active compounds (Mohammed and Salih, 2022). They have been employed in the development of drugs for various therapeutic areas, including neurodegenerative diseases, cancer, antimicrobial, antitumor, anti-inflammatory properties, and infectious diseases (Yang, et al, 2017;McKay, et al, 2011;Sandmeier and Carreira, 2021). In addition to their synthetic applications, nitrones also exhibit antioxidant properties, which make them useful in the fields of free radical biology and medicine (Floyd, et al, 2002;Floyd, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…N itrone is a kind of widely used 1,3-dipole in cycloadditions, giving various five-membered isoxazolidines, which have been well studied. 1,2 It was also found that 2ethynylphenyl-substituted nitrones could form other useful isoquinoline-containing cyclic azomethine ylides in the presence of transition metal salts, through N−O bond cleavage and the addition of imine to α-carbonyl carbenoid (Scheme 1a). 3 These cyclic azomethine ylides can be applied to the dipolar cycloadditions, leading to the easy construction of seven-membered nitrogen bridge rings.…”
mentioning
confidence: 99%